2014
DOI: 10.1002/2013jd020864
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian multimodel estimation of global terrestrial latent heat flux from eddy covariance, meteorological, and satellite observations

Abstract: Accurate estimation of the satellite-based global terrestrial latent heat flux (LE) at high spatial and temporal scales remains a major challenge. In this study, we introduce a Bayesian model averaging (BMA) method to improve satellite-based global terrestrial LE estimation by merging five process-based algorithms. These are the Moderate Resolution Imaging Spectroradiometer (MODIS) LE product algorithm, the revised remote-sensing-based Penman-Monteith LE algorithm, the Priestley-Taylor-based LE algorithm, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 118 publications
6
116
0
Order By: Relevance
“…One possible solution to address this inherent model limitation is to assemble a mosaicked product based on the predictive skill of the model(s) over particular biomes or climate zones. Another approach might be to develop an ensemble product using a suitable multi-model blending technique, such as a Bayesian Model Averaging approach (Hoeting et al, 1999;Yao et al, 2014). Either way, it is clear that further multi-model assessments are required for progressing global-scale flux characterisation and to ensure a robust and representative product is developed.…”
Section: Discussionmentioning
confidence: 99%
“…One possible solution to address this inherent model limitation is to assemble a mosaicked product based on the predictive skill of the model(s) over particular biomes or climate zones. Another approach might be to develop an ensemble product using a suitable multi-model blending technique, such as a Bayesian Model Averaging approach (Hoeting et al, 1999;Yao et al, 2014). Either way, it is clear that further multi-model assessments are required for progressing global-scale flux characterisation and to ensure a robust and representative product is developed.…”
Section: Discussionmentioning
confidence: 99%
“…Although we correct ET by Twine et al [43] method, the inaccuracy in the measured data still exists, such as the energy imbalance issue, with H + LE < R n − G (H: sensible heat flux; LE: latent heat flux) [61]. The mismatches in scale among different datasets may also lead to differences between the simulated and measured values.…”
Section: The Performance Of the Ms-pt Algorithm In Estimating Etmentioning
confidence: 99%
“…It is clear that equation (6) Because the original SEMI-Penman algorithm includes the variety of land cover (e.g., pastures, crop fields, forests) and the revised algorithm also considers the effects of the alpine meadow, we find the revised algorithm is sufficiently representative for the purpose of estimating terrestrial LE in the TRHR. In this study, the observed EC data is considered as accurately 'true' value to revise the LE algorithm, but approximately 20-50 W/m 2 of the EC measured errors and approximately 0.8 of energy closure ratio ((LE +H)/(R n − G)) will also lead to large uncertainties when estimating LE in the TRHR (Wilson et al 2002;Foken 2008;Mahrt 2010 Yao et al 2014a). This spatial mismatch between the flux tower site footprints and gridded footprints will also cause large uncertainties for LE estimation.…”
Section: Evaluation Of Algorithm Performance In Estimating Lementioning
confidence: 99%